Trends in Biomathematics: Modeling Cells, Flows, Epidemics, and the Environment Selected Works from the BIOMAT Consortium Lectures, Szeged, Hungary, 2019 /: Selected Works from the BIOMAT Consortium Lectures, Szeged, Hungary, 2019. (2020) - Unknown
No abstract available